Incorporating Radiation Oncology into Immunotherapy: proceedings from the ASTRO-SITC-NCI immunotherapy workshop. Issue 1 (29th January 2018) - Marciscano, Ariel E.; Walker, Joshua M.; McGee, Heather M.; Kim, Michelle M.; Kunos, Charles A.; Monjazeb, Arta M.; Shiao, Stephen L.; Tran, Phuoc T.; Ahmed, Mansoor M.
Abstract : Radiotherapy (RT) has been a fundamental component of the anti-cancer armamentarium for over a century. Approximately half of all cancer patients are treated with radiotherapy during their disease course. Over the two past decades, there has been a growing body of preclinical evidence supporting the immunomodulatory effects of radiotherapy, particularly when combined with immunotherapy, but only anecdotal clinical examples existed until recently. The renaissance of immunotherapy and the recent U.S. Food and Drug Administration (FDA) approval of several immune checkpoint inhibitors (ICIs) and other immuno-oncology (IO) agents in multiple cancers provides the opportunity to investigate how localized radiotherapy can induce systemic immune responses. Early clinical experiences have demonstrated feasibility of this approach but additional preclinical and clinical investigation is needed to understand how RT and immunotherapy can be optimally combined. To address questions that are critical to successful incorporation of radiation oncology into immunotherapy, the American Society for Radiation Oncology (ASTRO), the Society for Immunotherapy of Cancer (SITC) and the National Cancer Institute (NCI) organized a collaborative scientific workshop, Incorporating Radiation Oncology into Immunotherapy, that convened on June 15 and 16 of 2017 at the Natcher Building, NIH Campus in Bethesda, Maryland. This report summarizes key data and highlights from each session.